Thermoelastic Contact Problem of an Elastic Layer Resting on an Elastic Foundation - Srivastava, K. N.; Gupta, O. P. (Defence Science Journal, 2014)
This paper gives an analysis of the distribution stress in an infinite isotropic elastic layer, which rests on a semi-infinite isotropic elastic foundation and is indented by a rigid heated punch. The thermal and elastic properties of the layer and foundation are assumed to be different. Two problems are discussed. In the first problem the punch is a flat ended circular cylinder of unit radius, while in the second it is of conical shape. The problems are first reduced to dual integral equations, which are reduced to two Fredholm integral equations of the second kind. Iterative solutions of these equations are obtained for large value of h. Expressions for quantities of physical interest are derived.